2020
DOI: 10.1002/asia.202000746
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a Crown Ether/Amine‐Type Rotaxane as a Probe for the Versatile Detection of Anions and Acids by Thin‐Layer Chromatography

Abstract: A crown ether/amine-type [2]rotaxane was synthesized and utilized as a probe for the detection of acids and anions. The addition of acids to the amine-type [2]rotaxane solution generated corresponding crown ether/ammoniumtype [2]rotaxanes, which were purified by silica gel column chromatography as ammonium salts. The isolated yields of the [2]rotaxanes, possessing a variety of anions, depended on the acidity and polarity of the counter anions. The behaviours of the ammonium-type [2]rotaxanes on thin-layer chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
2
1
0
Order By: Relevance
“…In a variable‐temperature (VT) NMR study of the neutral [2]Rotaxane‐Phos , a translational movement of DB24C8 along the axle with the DB24C8 predominately located at the benzylaniline site (ca. 94 %) was observed (Figure S9a in the Supporting Information), which is in agreement with the published results [10d] . These observations indicated that the introduction of a phosphine functionality at the terminus of the axle did not affect the supramolecular properties of the [2]rotaxane.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In a variable‐temperature (VT) NMR study of the neutral [2]Rotaxane‐Phos , a translational movement of DB24C8 along the axle with the DB24C8 predominately located at the benzylaniline site (ca. 94 %) was observed (Figure S9a in the Supporting Information), which is in agreement with the published results [10d] . These observations indicated that the introduction of a phosphine functionality at the terminus of the axle did not affect the supramolecular properties of the [2]rotaxane.…”
Section: Resultssupporting
confidence: 91%
“…In addition to the main signals, similar to those of the neutral [2]Rotaxane‐Phos , small single signals around 6.6, 4.6, 4.5, 4.3, and 2.1 ppm characteristic of DB24C8 located at the dibenzylamine site were observed. This observation suggests the existence of a translational isomer (12 %) with DB24C8 located at the dibenzylamine region [10d] . In the 31 P NMR spectra recorded at lower temperatures, the doublet signal remained unchanged (Figure S20 in the Supporting Information), which indicates that the translational isomers were not distinguishable.…”
Section: Resultsmentioning
confidence: 95%
“…Finally, no sign of threading is observed for PA3 neither with DB24C8 nor TTFC8 within 14 days. These results are in good agreement with a recent study by Credi et al 19 which also showed the 3,5dimethyl phenyl moiety to be an efficient stopper in DB24C8 containing rotaxanes [37][38][39][40] and identified the 2,6-dimethyl phenyl moiety as kinetically inert to threading of DB24C8. 19 Consequently, out of these candidates we chose PA11 (1-naphthyl) as the most suitable pseudostopper for dualstimuli-induced switching experiments, because threading occurs at time intervals that are conveniently observable by NMR spectroscopy.…”
Section: Threading Experimentssupporting
confidence: 92%